2017
DOI: 10.22606/mcmr.2017.11005
|View full text |Cite
|
Sign up to set email alerts
|

Access to Medical Care for Individuals with Myalgic Encephalomyelitis and Chronic Fatigue Syndrome: A Call for Centers of Excellence

Abstract: The current study sought to better understand the experience of individuals with myalgic encephalomyelitis (ME) and chronic fatigue syndrome (CFS) in accessing care for their debilitating illness. Of 898 participants, less than half had ever seen an ME or CFS specialist, though 99% of participants were interested in specialist care. Participants cited geographic and financial barriers as most frequently precluding access to specialists. Furthermore, satisfaction with specialist care greatly exceeded satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 8 publications
4
27
0
Order By: Relevance
“…ME/CFS patients qualify as a medically underserved population by virtue of geographic and financial barriers to care (42). Both Tidmore et al (42) and Sunnquist et al (43) found: (a) areas of the United States in which there are no ME/CFS specialized care providers, (b) areas in which there are an inadequate number of specialized care providers, (c) areas in which there are an inadequate number of knowledgeable primary care providers, and (d) a national lack of educational opportunities for physicians and medical students to obtain the didactic and clinical experience necessary to diagnose and to treat ME/CFS.…”
Section: The Presentmentioning
confidence: 97%
See 2 more Smart Citations
“…ME/CFS patients qualify as a medically underserved population by virtue of geographic and financial barriers to care (42). Both Tidmore et al (42) and Sunnquist et al (43) found: (a) areas of the United States in which there are no ME/CFS specialized care providers, (b) areas in which there are an inadequate number of specialized care providers, (c) areas in which there are an inadequate number of knowledgeable primary care providers, and (d) a national lack of educational opportunities for physicians and medical students to obtain the didactic and clinical experience necessary to diagnose and to treat ME/CFS.…”
Section: The Presentmentioning
confidence: 97%
“…In 2006, then Director of the CDC Julie Gerberding launched a, “Spark Awareness,” campaign for ME/CFS which included a ME/CFS public awareness campaign, and the distribution of a CFS Toolkit for Health Care Professionals to aid in the diagnosis and treatment of ME/CFS (41). However, despite those efforts, the recent studies of Tidmore et al (42) and Sunnquist et al (43) have shown that definitive care of persons with ME/CFS in the United States is still lacking.…”
Section: The Pastmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, access to health care specialists is limited. Sunnquist, Nicholson, Jason, and Friedman (2017) found that of 898 participants, less than half had ever seen an ME or CFS specialist, though 99% of participants were interested in specialist care. Participants cited geographic and financial barriers as most frequently precluding access to specialists.…”
mentioning
confidence: 99%
“…Patients report difficulties in gaining access to medical care [29] and the vast majority of patients are dissatisfied with the quality of care received [30]. A study concluded: “Dissatisfied patients were significantly more likely to describe delay, dispute or confusion over diagnosis; to have received and rejected a psychiatric diagnosis; to perceive doctors as dismissive, sceptical or not knowledgeable about CFS [..]” [31].…”
Section: Due To the New Definition Of “Me/cfs” The Four Recommendamentioning
confidence: 99%